Implementasi Geointerpretasi berbasis Kearifan Lokal di Destinasi Wisata Minat Khusus Gua Cerme, Bantul, Yogyakarta - Kulsum, Farah Aida Ilmiatul; Djunaedi, Achmad (Gadjah Mada Journal of Tourism Studies, 2024)
One of the Gunung Sewu Geopark's three main pillars, geointerpretation of landscape duality, is implemented by special interest tour guides who possess the knowledge and abilities necessary for the job site and who must be proficient in cave exploration methods and cave science. With the primary tourist attraction being a cave with a tunnel length of 1200 meters and an underground river, this study was conducted at the Cerme Cave Tourist Destination, specifically in Srunggo Village, Imogiri District, Bantul Regency, to observe how the Pokdarwis Cerme tour guide implements interpretation in tourism spaces. The research was conducted utilizing a logical approach and qualitative approaches. Data gathering methods included cave and surface area mapping, cave photography, participant observation, and semi-structured interviews. The research findings show that there are two tourism spatial zonings that are related to the content of geointerpretation, and the second finding is interpretation activities of geological objects that are mixed with local wisdom through the story of the spread of Islam by the Wali Songo in Cerme, which is believed to have occurred in the past by the local community. This tale has been passed down through generations and is part of the material given to guests by Cerme Cave tour guides. These beliefs impact the destination's toponymy, ornaments and places within the cave, as well as geointerpretation activities carried out in the Cerme Cave Tourist Destination's dual landscape.